Problematic alcohol consumption among management undergraduates of Bhaktapur District, Nepal - Prashant Khadka; Anisha Chalise; Bhawana Kafle; Nirmal Raj Marasine; Shishir Paudel (BMC, 2024)
Abstract Background Alcohol consumption is a significant public health concern among young people worldwide. While alcohol use is culturally embedded in many Nepalese communities, evidence regarding the prevalence of problematic drinking and its associated factors remains scarce among youths. This study aims to assess the prevalence of alcohol consumption and problematic drinking and their associated factors among management undergraduate students of Bhaktapur, Nepal. Method A cross-sectional study was conducted among 304 undergraduate students in Bhaktapur, Nepal. The Alcohol Use Disorders Identification Test (AUDIT) was used to assess problematic drinking. Pearson's chi-square test and multivariable logistic regression analysis were performed to determine factors associated with alcohol consumption and problematic drinking, at the 5% level of significance. Results The prevalence of alcohol consumption was 58.2% (95% CI:52.0-63.6%), with 26.6% (95% CI: 19.2-33.1%) exhibiting problematic drinking. Being male (aOR: 2.05, 95% CI:1.11-3.76), dissatisfaction with academic performance (aOR: 2.43, 95% CI:1.35-4.38), and alcohol preparation at home (aOR: 2.54, 95% CI: 1.20-5.40) were associated with alcohol consumption. Problematic drinking was linked to male gender (aOR: 4.03, 95% CI: 1.71-9.46), living in a joint family (aOR: 2.40, 95% CI: 1.09-5.29), poor perceived emotional support from family (aOR: 4.94, 95% CI: 1.50-16.26), and traumatic experience (aOR: 2.68, 95% CI: 1.19-6.02). Conclusion This study revealed the concerning prevalence of alcohol consumption and dependency among Nepali undergraduate students. These findings highlight the need for comprehensive interventions targeting gender, the family environment, and academic factors to address alcohol misuse among Nepali youth.